If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 17x + -3 + -12 = 0.2(25x + -10) Reorder the terms: -3 + -12 + 17x = 0.2(25x + -10) Combine like terms: -3 + -12 = -15 -15 + 17x = 0.2(25x + -10) Reorder the terms: -15 + 17x = 0.2(-10 + 25x) -15 + 17x = (-10 * 0.2 + 25x * 0.2) -15 + 17x = (-2 + 5x) Solving -15 + 17x = -2 + 5x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-5x' to each side of the equation. -15 + 17x + -5x = -2 + 5x + -5x Combine like terms: 17x + -5x = 12x -15 + 12x = -2 + 5x + -5x Combine like terms: 5x + -5x = 0 -15 + 12x = -2 + 0 -15 + 12x = -2 Add '15' to each side of the equation. -15 + 15 + 12x = -2 + 15 Combine like terms: -15 + 15 = 0 0 + 12x = -2 + 15 12x = -2 + 15 Combine like terms: -2 + 15 = 13 12x = 13 Divide each side by '12'. x = 1.083333333 Simplifying x = 1.083333333
| 3xy(5xy)+3xy(1)= | | 16t^2+150t+20=0 | | 5x+2=36 | | .5x-.625=.75x+.375 | | 2x(x-4)+x(3-2x)= | | 13r+4-7r= | | -2+ln(x-4)=4 | | 5x+10x+5=25 | | 5x+10x+5=25 | | 5x+10x+5=25 | | 2B-6=4B | | 3-(3x-8)=4y-5 | | (4c-6c+5)(4c-2c-1)= | | lnx-2lnx=3 | | 6x-4=20x+3 | | 6x-23+x+54=180 | | 4x+2x(x+4)= | | -4x-6(-2+4)=64 | | 2x+y-z=7z | | -4x-6(-2+4)=64 | | 3x-1=-3x+3 | | 3x-1=-3x+3 | | -5x+-2=-2X+4 | | -6x-5(-3x-3)=60 | | 114=2x+3x | | 5x+7y=3890 | | 8x+7y-5-5x+6y-3= | | -2x-2(-5x-4)=-80 | | 15+4y-1=15y-13-2y | | y+(y-2)2=2 | | 3x-n=7+n | | 25-13=3(x-1) |